DETERMINATION OF MICELLE STRUCTURE AND CHARGE BY NEUTRON SMALL-ANGLE SCATTERING - Hayter, J; Penfold, J (Steinkopff-Verlag, 1983)
We present a general method of determining the structure and charge of globular ionic micelles, using neutron small-angle scattering. The micellar solutions may have any concentration within the micellar phase. The method is based in part on an analytic calculation of the interparticle correlations between monodisperse spherical micelles, and we discuss the theory in some detail to justify its application to polydisperse globular particles. Experimental results are presented for several cationic and anionic micellar systems. © 1983 Steinkopff.